Who Are You to Me? Relational Distance to Victims and Perpetrators Affects Advising to Report Rape. (March 2022) - Puthillam, Arathy; Parekh, Aneree; Kapoor, Hansika
The victim's decision to report a crime is generally dependent on the advice received from a confidant. The effects of a confidant's relationship to victims and perpetrators on the advice given to report rape were investigated. Indian participants ( N = 418) read one of the seven scenarios of acquaintance rape as a confidant; the scenarios depicted different relationships between the victim and perpetrator (family vs. friend vs. stranger). Confidants closer to victims were more likely to advise reporting, whereas confidants closer to the perpetrator were less likely to advise reporting. Rape myth acceptance and victim blaming negatively predicted reporting to agencies.